Kesesuaian Lahan Tambak Budidaya Ikan Bandeng (Channos channos) Di Desa Limbula - Indrawan Abas; Arafik Lamadi; Indra G. Ahmad (Transbahasa, 2026)
Limbula Village is one of the areas in Pohuwato Regency that has potential for milkfish aquaculture. It is known that in aquaculture activities, site selection is a crucial factor influencing pond construction and durability, maintenance costs, and the level of production productivity. Therefore, pond land suitability becomes an important factor that needs to be analyzed for its feasibility. This study aimed to determine the suitability of land quality in two milkfish ponds in Limbula Village, as well as the limiting factors affecting it. The study was conducted for four weeks in Limbula Village, Wanggarasi District, Pohuwato Regency. The research method used was observation, carried out through direct measurement of water and soil parameters at the study sites. Data analysis employed a scoring method using a weighted index to assess and determine the level of suitability of milkfish ponds. The measurement results obtained for Pond 1 and Pond 2 were temperatures of 32.3°C and 32.0°C, pH values of 8.6 and 8.7, dissolved oxygen levels of 3.92 mg/L and 4.32 mg/L, water depth of 82 cm, water transparency of 31 cm and 32 cm, salinity of 38 ppt and 39 ppt, ammonia concentrations of 0.67 mg/L and 0.71 mg/L, soil pH values of 5.6 and 5.5, organic matter contents of 0.033 and 0.034, and silty clay and silty loam soil textures, respectively. The scoring results showed values of 61 for Pond 1 and 63 for Pond 2. Both ponds in Limbula Village were classified as moderately suitable (S2). The limiting factors affecting land quality in both ponds were temperature, salinity, ammonia, and organic matter.